Educating for Response-able counselling - Hangue, William J. (Canadian Journal of Counselling and Psychotherapy, 2011)
The ability to account for where one stands and what one does is integral to counsellor education. This paper explores several principles of responsibility as expressed in the counsellor education program at the University of Alberta. This is followed by a brief description of how these principles are carried out in practice.